Groundwater in the District of Wajo is stored in Siwa-Pompanua basin covering an area of 93,900 ha and discharge of around 379 millions m3/yr. The groundwater is utilized to irrigate rain-fed rice fields privately by farmers by means of wells. The distance between wells and pumping rate are designed without considering the characteristics of the aquifer and adequate irrigation management so that damage in environment might occur and consequently farming might not be sustainable. A research wa - Suhardi .; Hidayat Pawitan; Budi Indra Setiawan; Roh Santoso B. Waspodo (Forum Pasca Sarjana, 2008)
Groundwater in the District of Wajo is stored in Siwa-Pompanua basin covering an area of 93,900 ha and discharge of around 379 millions m3/yr. The groundwater is utilized to irrigate rain-fed rice fields privately by farmers by means of wells. The distance between wells and pumping rate are designed without considering the characteristics of the aquifer and adequate irrigation management so that damage in environment might occur and consequently farming might not be sustainable. A research was conducted with the objectives to study the aquifer characteristics and to develop environmentally friendly groundwater management. Mathematical models were developed by combining equations of conservation of fluid mass (continuity equations) and Darcy’s law, whereas models of groundwater management were based on crop water requirement and aquifer characteristics. Test of the model resulted in coefficient of determination equal to 0.848 for the prediction of the drawdown groundwater head. The result of the model optimization indicated the optimum discharge of each of the wells was different. One of the wells had a the biggest discharge of 1,268.33 m3/day irrigating 27.58 ha and one other of the wells had a the smallest discharge of 279.54 m3/day irrigating 6.08 ha of paddy fields based on the irrigation water requirement of 45.99 m3/ha.day. The reasonable minimum area (ha) determined with equation of power function in x, where x are irrigated hours per season. For one of planting season/yr, the coefficients of the power (α) equal to 0.0123 and the power functions (β) equal to 0.7247, while for two of planting season/yr with α equal to 0.0047 and β equal to 0.8413. Key words: sustainable groundwater utilization, paddy field irrigation, groundwater management model